Perbandingan Komplikasi Malunion pada Pasien Fraktur Humerus Pasca Terapi Operatif dan Non-Operatif di RS Bina Sehat - Djaya Mario Eri Surya Alfonsus; Muhamad Hasan; Erfan Efendi (Pustaka Kesehatan, 2014)
Humerus fracture is a quite common fracture. Fracture of diaphyseal humerus is 1,2 % of all cases of fracture. The treatment of humeral shaft fracture can use 2 different approaches, operative treatment and conservative treatment. This research aimed to compare the complication of malunion in patients with operative and conservative treatment. This was an observational analytic study on patients at the Bina Sehat Hospital. Samples were divided into 2 groups, operative and non-operative. Both groups were examined by measuring the lenght of the humerus after fracture comparing with its contralateral, the ability of the internal rotation, the ability of the external rotation, and angulation inspection. Statistical test showed a difference humerus shortening between 2 groups reached 0.873 cm. The difference between 2 groups on the ability of internal rotation reached 11.4710. The difference between 2 groups on ability of external rotation reached 16.608o. And the result for angulation assessment also showed significant difference between 2 groups. In conclutson, there was a significant difference in complications of malunion between operative and non-operative groups.   Keywords: humerus fracture, operative treatment, non operative treatment, comparative malunion